Developing Halal Tourism Destinations in Kitakyushu, Japan: An International Community Service Collaboration - Muhammad Hamdi; Hendro Widodo (IJECS: Indonesian Journal of Empowerment and Community Services, 2026)
ABSTRACT The rapid global growth of Muslim travellers has created substantial opportunities for non-Muslim destinations to develop halal tourism infrastructure. However, empirical accounts of how university–diaspora community–government collaborations can be operationalised systematically in Japanese secondary cities remain scarce. This international community service project aimed to: (1) develop comprehensive halal tourism packages for Kitakyushu; (2) produce professional promotional content; and (3) build the capacity of PCIM (Special Branch of Muhammadiyah) Japan members to establish and manage sustainable halal tourism enterprises. The project adopted a Participatory Action Research (PAR) approach over six months (May–October 2025) across three phases. Data were collected through three focus group discussions (18 participants), semi-structured in-depth interviews with 12 key stakeholders, structured field observations at nine destinations, and document review; instruments comprised an FGD guide, interview protocol, and observation checklist, all expert-validated. Success indicators were specified at three levels: outputs (packages, content, business proposals), outcomes (pre-/post-test knowledge gains), and early impact (partner follow-up commitments). The project produced three segmented halal tourism packages, a four-minute promotional video. The scholarly contribution lies in articulating an operational model of cross-border collaboration grounded in Islam Berkemajuan values that integrates diaspora empowerment, cultural adaptation, and Sustainable Development Goal 17 (SDG 17).   Keywords: Community service, Halal tourism, International collaboration, Japan, Muhammadiyah, Community-based tourism.